2015
DOI: 10.1007/978-3-319-24462-4_9
|View full text |Cite|
|
Sign up to set email alerts
|

A New Feature Selection Methodology for K-mers Representation of DNA Sequences

Abstract: DNAsequence decomposition into k-mers and their frequency\ud counting, defines a mapping of a sequence into a numerical space by a numerical\ud feature vector of fixed length. This simple process allows to compare\ud sequences in an alignment free way, using common similarities and\ud distance functions on the numerical codomain of the mapping. The most\ud common used decomposition uses all the substrings of a fixed length k\ud making the codomain of exponential dimension. This obviously can affect\ud the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As such, recently developed alignment-free methods [21] holds a promising approach to study regulatory genome. For feature extraction as spectral representation, several studies have shown significant research on DNA sequences [22], [23] based on the performances of conventional machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…As such, recently developed alignment-free methods [21] holds a promising approach to study regulatory genome. For feature extraction as spectral representation, several studies have shown significant research on DNA sequences [22], [23] based on the performances of conventional machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…These sequence alignment methods involve a feature selection stage. Spectral representation of DNA sequences can be used to determine the sequence similarity in order to enhance the classification performance [8,9]. The time computational complexity remains the reason for restricting the use of alignment approaches.…”
Section: Introductionmentioning
confidence: 99%